2011
DOI: 10.1186/1471-2202-12-97
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic mouse model for the formation of Hirano bodies

Abstract: BackgroundHirano bodies are actin-rich cytoplasmic inclusions found predominantly in the brain in association with a variety of conditions including aging and Alzheimer's disease. The function of Hirano bodies in normal aging and in progression of disease has not been extensively investigated due to a lack of experimental model systems. We have developed a transgenic mouse model by expression of a gain-of-function actin cross-linking protein mutant.ResultsWe used the Cre/loxP system to permit tissue specific e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 57 publications
0
30
4
Order By: Relevance
“…Interestingly, despite the important role of actin in LTP, we found that there was no measurable difference between R26CT and R26CT-CRE mice at either 3 or 8 months of age (Figure 10) in the ventral hippocampus. These results are in contrast with those observed in our earlier study in which R26CT x Thy1.2-CRE mice showed a deficit in the early, but not the late phase LTP [28]. Thus, presence of model Hirano bodies in the CA1 region of the ventral hippocampus of R26CT-CRE mice (current R26CT × CamKIIa-CRE mouse) appears to have negligible effects on synaptic plasticity as assessed by pairedpulse and LTP measurements.…”
Section: Effect Of Hirano Bodies In the Ca3 And Ca1 Regions Of The Hicontrasting
confidence: 56%
See 4 more Smart Citations
“…Interestingly, despite the important role of actin in LTP, we found that there was no measurable difference between R26CT and R26CT-CRE mice at either 3 or 8 months of age (Figure 10) in the ventral hippocampus. These results are in contrast with those observed in our earlier study in which R26CT x Thy1.2-CRE mice showed a deficit in the early, but not the late phase LTP [28]. Thus, presence of model Hirano bodies in the CA1 region of the ventral hippocampus of R26CT-CRE mice (current R26CT × CamKIIa-CRE mouse) appears to have negligible effects on synaptic plasticity as assessed by pairedpulse and LTP measurements.…”
Section: Effect Of Hirano Bodies In the Ca3 And Ca1 Regions Of The Hicontrasting
confidence: 56%
“…Thus, presence of model Hirano bodies in the CA1 region of the ventral hippocampus of R26CT-CRE mice (current R26CT × CamKIIa-CRE mouse) appears to have negligible effects on synaptic plasticity as assessed by pairedpulse and LTP measurements. Once again, the presynaptic expression of model Hirano bodies in the CA3 of the Thy1.2-CRE mouse resulted in significant effects in the former report [28] that were not observed with the postsynaptic expression pattern in the CA1 of the current CAMKIIa-CRE mouse.…”
Section: Effect Of Hirano Bodies In the Ca3 And Ca1 Regions Of The Himentioning
confidence: 80%
See 3 more Smart Citations